The Effect of Iron Oxide on the Mechanical and Ageing Properties of Y-TZP Ceramic - Sivakumar, Sivanesan; Teow, Hsien Loong; Ramesh, Singh; Niakan, Ali; Mase, Nobuyuki (Trans Tech Publications, 2016)
A small amount of iron oxide (Fe2O3) was added to the commercially available 3 mol% Y-TZP as a sintering aid over a temperature range of 1250°C to 1500°C. Sintered samples were then evaluated to determine the bulk density, Vickers hardness, and fracture toughness. In addition, hydrothermal ageing experiments to determine the tetragonal phase stability were performed on selected sintered samples in superheated steam at 180°C / 10 bar for up to 24 hours. Based on the work carried out, it was revealed that additions of Fe2O3 particularly 0.3 wt% was indeed beneficial in aiding densification, improving the matrix stiffness and hardness when compared to undoped Y-TZP sintered at temperatures below 1350°C. Addition of Fe2O3 was found to have negligible effects on the fracture toughness of all samples with the exception of the 0.5 and 1 wt% doped Y-YZP sintered above 1400°C. Hydrothermal ageing resistance of Y-TZP was found to be enhanced with the addition of Fe2O3 in the Y-TZP matrix.